Terekeme (Karapapak) Türkleri ve Mânileri (Bayatıları/Mahnıları): Muş-Bulanık Çevresi / Terekeme/Karapapak Turks and their Quatrains Called as Mani/Mahnı or Bayatı (Muş-Bulanık District) - KEMALOĞLU, MUHAMMET (Journal of History Culture and Art Research, 2013)
Abstract Manis, which are called with different names in the geography of Anatolia, show similarities in terms of form and content in general. Mani read within a particular tradition also reflects poetry taste of the Turkish people ideally. This study benefits from the data of field research that we have done. Mani and the tradition of reading Mani which has been got through compilation in the field, transmitted from generation to generation, which has specific rules and reflects the mentality, love, longing, feeling, and behavior of local people and culture of the region are going to form the main part of the study. In addition to this, characteristics of Terekeme (Karapapak) Turks’ dialect are also dwelled on. Öz Anadolu coğrafyasında farklı isimlerle zikredilen mâniler, şekil ve muhteva açısından genel olarak benzerlikler göstermektedir. Belirli bir gelenek dâhilinde söylenen mâniler, Türk halkının şiir zevkini de en güzel şekilde aksettirmektedir. Bu çalışmada yapmış olduğumuz saha araştırmasının verilerinden yararlanılacaktır. Çalışmanın esas bölümünü; sahada derlemeler yoluyla elde edilmiş, kuşaktan kuşağa aktarılan, belirli kuralları olan, yöre insanının; düşünce yapısını, sevdalarını, özlemlerini, duygu ve davranışlarını, yörenin kültürünü yansıtan maniler ve mani anlatma geleneği oluşturmaktadır. Bunun yanı sıra Terekeme (Karapapak) Türklerinin ağız özellikleri üzerinde de durulmuştur. Les turcs de Terekeme (Karapapak) et leurs qutrains (region de Muş-Bulanık) Résumé Les manies appelées par des noms différents en Anatolie, présentent des ressemblances en terme de forme et de contenu. Les manies, qui se disent dans une tradition particulière, reflètent aussi le plus bel exemple de la poésie du peuple turc. Dans cette étude, nous allons utiliser les données de notre recherche de terrain. La partie fondamentale du travail consiste en manies et la tradition du récit des manies acquises au moyen du travail de terrain, transmis de génération en génération, avec des règles spécifiques et en reflétant la structure de la pensée des gens de la région, leurs aspirations, leurs sentiments, leurs attitudes et comportements et leur culture. En outre, on va aussi analyser les caractéristiques de bouche des Turcs de Terekeme (Karapapak)